EDUKASI COVID-19 DAN UPAYA PENCEGAHANNYA PADA MASYARAKAT DI KECAMATAN KOTA JUANG KABUPATEN BIREUEN, ACEH - Renny Eka Putri; Rauzatul Mirizal Jannah (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
One way to prevent Covid-19 is through educational activities and information dissemination useful for people who are still unfamiliar with information related to Covid-19. Pulo Kiton is one of the villages in Juang City, Bireuen Regency, Aceh Province. Based on the level of economic growth of the village from year to year, it can be said to be developing. Pulo Kiton Village's economic activities are dominated by the home industry sector and other formal businesses. This activity aims to increase public knowledge regarding Covid-19 prevention measures. The activities carried out were making and distributing hand sanitizers, making banners, leaflets, and Covid-19 posters for public education, and sharing bread in the form of caring for others. This activity can be carried out correctly and with the support of the Village Head and the local community, and there are no significant obstacles because Bireuen Regency is a Covid-19 green zone. However, the prevention of Covid-19 is still carried out according to health protocols. Another supporting activity is training in making liquid dishwashing soap, and this activity can help increase the community created to help develop businesses. Another activity is the use of yardland by planting a family medicinal plant because this village does not have plantation land. Hence, yard land is an option for carrying out activities. Another supporting activity is the manufacture of liquid organic fertilizer from coconut water waste. Homemakers can use this fertilizer for the growth of ornamental plants in the yard. The multimedia activities carried out are making video tutorials on making fertilizer and making bean sprouts without tails. The results of this complex activity can increase public knowledge in preventing Covid-19 and provide skills and solutions amid the Covid-19 pandemic.